MATING BEHAVIOUR OF CROCIDOLOMIA PAVONANA F. - Purwatiningsih Purwatiningsih; Mirza Devara (UNEJ e-Proceeding, 2016)
The sequence and duration of mating behaviour Crocidolomia pavonana were observed and investigated by using ethogram time budgets. This research was conducted in the dark hours from 18:00 pm to 06.00 am. The results showed that C. pavonana mating behaviour consists of calling behaviour , courtship behaviour, copulation and oviposition behaviour. Behaviour of copulation was dominated among other behaviour. It took about 48% of on all mating steps behaviour. However, the frequency of the calling leaded by 70.8 times among other behaviour.